2019
DOI: 10.1155/2019/9017951
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vitamin D Status and Its Effect on Vitamin D Levels in Early Infancy in a Tertiary Care Centre in Sri Lanka

Abstract: Epidemiologic studies from South Asian countries have reported vitamin D deficiency among all age groups. However, there is very little information on vitamin D levels, especially in the vulnerable populations (pregnant/breast feeding mother and infants) in Sri Lanka. More data on vitamin D status of such populations will be important for policy decisions to be made at a national level. Similarly, it will be valuable for healthcare programs in other countries (e.g., United States, Australia, Europe, and Canada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Vitamin D supplementation is not routinely carried out in Sri Lanka despite reports of vitamin D deficiency among various age groups. A single-centre, hospital-based study in the Colombo district had reported vitamin D deficiency (<20 ng/ml) without clinical features of rickets or osteomalacia among pregnant (62.9%) and lactating women (49.5%) and in infants (88.6%) [11]. A recent study conducted in a community setting in the Colombo district among pregnant women in their third trimester Case Reports in Pediatrics (unpublished) showed 62.1% of subclinical deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D supplementation is not routinely carried out in Sri Lanka despite reports of vitamin D deficiency among various age groups. A single-centre, hospital-based study in the Colombo district had reported vitamin D deficiency (<20 ng/ml) without clinical features of rickets or osteomalacia among pregnant (62.9%) and lactating women (49.5%) and in infants (88.6%) [11]. A recent study conducted in a community setting in the Colombo district among pregnant women in their third trimester Case Reports in Pediatrics (unpublished) showed 62.1% of subclinical deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…They further suggested the dose of 4000 IU per day, which is equal to the amount of vitamin D obtained by sun exposure. Low levels of maternal vitamin D have known to be a risk factor of Vitamin D deficiency/ insufficiency in infants and breastfeeding children [19].…”
Section: Discussionmentioning
confidence: 99%
“…The registered pregnant women are followed up from the first trimester and referred to the local hospital for delivery [15]. The sample size was calculated, taking a ±5% margin of error, P of 63.4 [16], and a confidence level of 95%.…”
Section: Study Design and Participantsmentioning
confidence: 99%